C16 Peptide Promotes Vascular Growth and Reduces Inflammation in a Neuromyelitis Optica Model - Chen, Haohao; Fu, Xiaoxiao; Jiang, Jinzhan; Han, Shu (Frontiers in Pharmacology, 2019)
The goal of this study was to elucidate the mechanism of action of C16, a laminin-1 peptide that competes with αvβ3 for integrin binding, in treating neuromyelitis optica (NMO). A neuromyelitis optica (NMO) rat model was established and specific inhibitors were used to investigate the effect of Tie2 kinase, integrin, and PI3K/Akt signaling pathways on C16 function in NMO using histological, immunohistochemical, immunofluorescence, western blot, and ELISA assays. A total of 135 rats were divided into 5 groups: control untreated group (n =15) and 4 test groups (n = 30 per group) including vehicle treated control, C16, Tie2 kinase inhibitor + C16, and PI3K/Akt inhibitor LY294002 + C16. We found that inhibiting Tie2 kinase resulted in partial loss of C16 peptide-mediated effects, while suppressing PI3K/Akt signaling reduced C16 peptide-mediated effects. In addition, activation of the αvβ3 integrin axis and Tie2 kinase promoted PI3K/Akt signaling. Our study showed that the Tie2-PI3K/Akt, Tie2-integrin, and integrin-PI3K/Akt signaling pathways regulate C16 peptide function in vascular growth and stabilization as well as inflammation in NMO.